Cover Feature: Scalable Photocatalyst Panels for Photoreforming of Plastic, Biomass and Mixed Waste in Flow (ChemSusChem 19/2021). Issue 19 (15th September 2021) - Uekert, Taylor; Bajada, Mark A.; Schubert, Teresa; Pichler, Christian M.; Reisner, Erwin
Abstract : The Cover Feature shows a photoreforming process that cleans up waste (plastic, biomass, food, mixed) to provide a cleaner, hydrogen‐powered world. This process operates in flow and uses only sunlight and a photocatalyst panel to continuously generate hydrogen fuel from waste and water. More information can be found in the Full Paper by T. Uekert et al .